Theoretical Study of Oxygen Atom Adsorption on A Polycyclic Aromatic Hydrocarbon Using Density-Functional Theory - Mokhammad Fajar Pradipta; Harno Dwi Pranowo; Viny Alfiyah; Aulia Sukma Hutama (Universitas Gadjah Mada, 2021)
Potential energy curves (PECs) and energy profiles of atomic O attack on coronene as a model for graphene/graphitic surface and interstellar reaction surface have been computed at the unrestricted B3LYP/cc-pVDZ level of theory to elaborate on atomic O attack mechanism and chemisorption on coronene. The PECs were generated by scanning the O atom distance to the closest carbon atom on